Crumpled graphene with graded interlayer spacing for high-rate Na+ storage - Liu, Xiaoxu (2024)
In electrode preparation, graphene-based electrodes usually form a uniaxially oriented stacking structure, which limits the Na+ diffusion in graphene electrodes for sodium-ion batteries (SIBs). In this work, a crumpled graphene (CG) anode with graded interlayer spacings was synthesized, and CG exhibits high-rate performance for SIBs. The CG has a folding microstructure like a paper clip that facilitates rapid adsorption/desorption of Na+ on its surface so that the diffusion kinetics of Na+ could be improved. The x-ray absorption fine structure and transmission electron microscope proved the mechanism of Na+ co-adsorption and explained the reason for its high-rate performance. When the three-dimensional CG is used as the anode of SIBs, it has a high-rate performance of 146 mAh g−1 with the current density increasing to 1 A g−1, and CG still maintained about 79 mAh g−1 after 1000 cycles at 0.5 A g−1 with good structural stability.